EFFECT OF SUPPLEMENTING DIFFERENT LEVELS OF CONJUGATED LINOLEIC ACID (CLA) TO THE DIET ON PRODUCTIVE PERFORMANCE OF BROILER CHICKEN - & Qasim, Al-Bandr (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was carried out at Poultry Research Station, State Board of Agricultural Research, Ministry of Agriculture for the period from 27 September 2014 to 9 November 2014 to evaluate the Supplementation of different levels of Conjugated Linoleic Acid (CLA) on productive performance of broiler. Four hundred eighty chicks (Ross-308),one day old were randomly distributed to four dietary treatments for 42 days of age with 3 replicates/vtreatment (40 bird/replicate). Experimental treatments were as follow; T1 (Control diet) without supplement, while the treatment T2,T3 and T4  were Supplemented with 1, 1.5, 2 g CLA /kg diet  respectively. The results showed significant (P ≤ 0.05) increased in mean of body weight, weight gain, average feed consumption and the feed conversion ratio, for the birds of treatments T3 and T4 in comparison with control treatment (T1). A     significant (P ≤ 0.05) improvement was found in dressing percentage of treatments T3 and T4  in comparison with control treatment, whilst the breast percentage was significantly higher in all treatments which supplemented CLA than T1 treatment. The liver percentage weight has significantly (P ≤ 0.05) increased whereas the abdominal fat percentage has significantly (P ≤ 0.05) decreased in treatment T4 in comparison with control treatment. It is concluded that CLA supplementation at levels 1.5 and 2 g/kg diet of broiler chicken has improved productive performance.